2013
DOI: 10.1186/1475-2875-12-387
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine response to pregnancy-associated recrudescence of Plasmodium berghei infection in mice with pre-existing immunity to malaria

Abstract: BackgroundDuring childhood, residents of areas with stable transmission of Plasmodium falciparum parasites acquire substantial protective immunity to malaria, and adults therefore rarely experience clinical disease episodes. However, susceptibility to infection reappears in pregnant women, particularly primigravidae. This is due to appearance of antigenic parasite variants that are restricted to pregnancy. Variant-specific immunity also governs pregnancy-associated recrudescence of Plasmodium berghei infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…These observations corroborate previous findings in Africa where high plasma levels of IL-10 were associated with malaria infection during pregnancy (Kabyemela et al, 2008;Nmorsi et al, 2010;Boström et al, 2012;Chandrasiri Upeksha et al, 2013;Chêne et al, 2014). High IL-10 levels have also been reported in mice models during pregnancy malaria (Megnekou et al, 2013). Although no significant correlation was observed between CXCL-10 levels and parity, the level of this chemokine was high irrespective of gravidity.…”
Section: Discussionsupporting
confidence: 93%
“…These observations corroborate previous findings in Africa where high plasma levels of IL-10 were associated with malaria infection during pregnancy (Kabyemela et al, 2008;Nmorsi et al, 2010;Boström et al, 2012;Chandrasiri Upeksha et al, 2013;Chêne et al, 2014). High IL-10 levels have also been reported in mice models during pregnancy malaria (Megnekou et al, 2013). Although no significant correlation was observed between CXCL-10 levels and parity, the level of this chemokine was high irrespective of gravidity.…”
Section: Discussionsupporting
confidence: 93%
“…However, the suggestion from our data, as discussed above, of a suppressive effect of P. falciparum infection, reflected by the concentrations of different T cell-derived cytokines in placental plasma at delivery, requires further investigation in this context. There are striking similarities, furthermore, between our findings concerning cytokine concentrations and those of a recently published study using a murine model of placental malaria infection (34). This appears to strengthen the idea that infection-related suppression of T cell activity-regardless of whether it is the cause or the effect-may play a role in determining pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 62%
“…The delayed parasitemia patency coupled with prolonged parasitemia suppression and survival time in the treatment groups may be due to the high IFN-γ and TNF-α levels present prior to challenge infection. This observation has been reported in previous studies where clearance of blood stage infection coincides with high IFN-γ levels [ 23 , 26 , 27 ]. Other studies have equally confirmed the involvement of TNF-α in Plasmodium clearance [ 24 ], [ 25 ].…”
Section: Discussionsupporting
confidence: 87%